Tobacco use and oral hygiene as risk indicators for periodontitis - Amarasena N, Ekanayaka AN, Herath L, Miyazaki H. (Blackwell Synergy, 2002)
To detect the periodontal status of male smokers and betel chewers in a rural community in Sri Lanka and compare it with that of male nontobacco users of the same community.